1986
DOI: 10.1159/000309679
|View full text |Cite
|
Sign up to set email alerts
|

The Normal Visual Field on the Humphrey Field Analyzer

Abstract: To provide a bank of normal perimetric data, we tested the central and peripheral visual fields of 102 novice normal subjects using the Humphrey automated perimeter. All eyes used for visual field testing were first carefully examined to be sure that they were, indeed, normal. We calculated population means and standard deviations of each test location and for each decade for age. Average differential light sensitivity decreased with advancing age: ––0.5 dB/decade at fixation, ––0.6 dB/decade in the central (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
3

Year Published

1987
1987
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 5 publications
(10 reference statements)
7
47
0
3
Order By: Relevance
“…Several investigations (1)(2)4,7,10,12) have found a lower visual sensitivity in superior hemifield compared with the inferior one, which is also in agreement with our results (Table 7). It is also remarkable that this difference of visual sensitivity may not be explained by a possible blepharoptosis, once in previous and present studies those subjects had been excluded from the evaluation.…”
Section: Influence Of Eccentricitysupporting
confidence: 93%
See 2 more Smart Citations
“…Several investigations (1)(2)4,7,10,12) have found a lower visual sensitivity in superior hemifield compared with the inferior one, which is also in agreement with our results (Table 7). It is also remarkable that this difference of visual sensitivity may not be explained by a possible blepharoptosis, once in previous and present studies those subjects had been excluded from the evaluation.…”
Section: Influence Of Eccentricitysupporting
confidence: 93%
“…Data provided by the current study are in accordance with those reported by several investigators (2,4,(7)(8)(9)(10) concerning visual sensitivity significant decrease with age, even using differentiated autoperimeters, strategies, programs and examination conditions. It is important to remark that a study (6) undertaken with normal subjects (n=562) divided into non-homogeneous age groups was not able to show that the non-linear function, with R 2 superior to the others, was statistically better than the linear one.…”
Section: Average Retinal Sensitivity and Agesupporting
confidence: 92%
See 1 more Smart Citation
“…(1) appraisal of the hill of vision at each test location of the stimulus grid individually (Goldmann 1945;Brenton & Phelps 1986;Iwase et al 1988;Zulauf et al 1994a;Koller et al 2001), disregarding the correlation between neighbouring points (Lachenmayr et al 1995), or (2) introduction of VF indices for the averaging of threshold values over certain VF areas (Haas et al 1986;Katz & Sommer 1986;Lachenmayr et al 1994;Zulauf et al 1994b), disregarding local characteristics of the VF.…”
Section: Discussionmentioning
confidence: 99%
“…*Participants with peripheral vision loss who were not able to complete the auditory-visual localization task in peripheral space. Sensitivity (DLS) from 36° to 1° (Brenton & Phelps, 1986). The luminance of the visual stimulus was also increased for participants with vision loss, where necessary, to increase the reliability of the visual stimulus.…”
Section: Apparatus and Stimulimentioning
confidence: 99%